Weathered soft rock road curing and stabilizing material and preparation method thereof
By using specific formula curing agents in weathered soft rock road curing stabilized materials, the water stability performance and compressive strength of the material are improved, and the problems of prone to disintegration and carbon emissions of strong weathered soft rocks are solved, and a more stable roadbed is achieved Structural and environmentally friendly production process.
Patent Information
- Application Number
- CN202411292868.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
AI Technical Summary
Strong weathered soft rocks are prone to disintegration when exposed to water, and poor water stability performance, resulting in roadbed compression settlement and structural instability. Traditional curing methods such as the use of cement and lime will lead to poor carbon emissions and curing effects.
The preparation method of weathered soft rock road curing stabilized materials is adopted, and the curing agent composed of silicate cement clinker powder, composite mineral blend, Glauber's salt gypsum, quicklime and sodium dodecyl benzene sulfonate are used to pass the specific Formulation ratio and process steps to improve the water stability and compressive strength of weathered soft rocks, and reduce carbon emissions.
The water stability performance and unbounded compressive strength of weathered soft rock road cured stable materials are significantly improved, the carbon emissions in the production process are reduced, and the problems of roadbed compression settlement and structural instability are avoided.
Smart Images

Figure CN119143445A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of road engineering materials, in particular to a production technology of weathered soft rock road solidification and stabilization materials. Background Art
[0002] The highly weathered soft rock widely distributed in Chengdu, Sichuan, shows poor water resistance, which is manifested in rapid disintegration and softening when exposed to water, as well as rapid attenuation of strength. If directly used as roadbed filling materials, it is very easy to induce serious engineering diseases such as significant roadbed compression settlement, roadbed structural instability, and bridge abutment jumping. Traditionally, cement and lime are used as the main additives for the solidification treatment of this type of soil. However, the production process of such materials is accompanied by a large amount of carbon emissions, and the solidification effect is poor when directly used for the solidification treatment of weathered soft rocks.
[0003] The technical issues that need to be resolved at present:
[0004] 1. Strongly weathered soft rock is prone to collapse when exposed to water and has poor water stability. If it is directly used as roadbed filling material, it is very easy to induce significant compression settlement of the roadbed and instability of the roadbed structure.
[0005] 2. Strongly weathered soft rock is directly used for roadbed. In the case of no cementation and solidification, its unconfined compressive strength is low and cannot meet the application requirements of roadbed base.
[0006] 3. Although cement and lime can also be used to solidify strongly weathered soft rocks, the production process of such materials is accompanied by a large amount of carbon emissions, and when directly used for the solidification of weathered soft rocks, it often leads to adverse consequences such as roadbed cracking. Summary of the invention
[0007] In order to improve the water stability and unconfined compressive strength of weathered soft rock road solidification and stabilization materials and reduce carbon emissions in the production process, the present invention provides a weathered soft rock road solidification and stabilization material and a preparation method thereof.
[0008] The technical scheme adopted by the present invention is: a preparation method of weathered soft rock road solidification stabilization material, the production raw material formula comprises the following components in mass proportion: 100 parts of strongly weathered soft rock, 5-10 parts of curing agent; the curing agent is composed of the following components in mass proportion: 100 parts of silicate cement clinker powder, 100-150 parts of composite mineral admixture, 30-45 parts of mirabilite gypsum, 20-36 parts of quicklime, 2-9 parts of sodium dodecylbenzene sulfonate, and 0.08-0.6 parts of monoethanol diisopropanolamine; the composite mineral admixture is composed of granulated blast furnace slag powder and lithium slag powder in a mass ratio of 1.5-3.5:1.
[0009] Description of some raw materials:
[0010] The mirabilite gypsum in the present invention refers to the by-product produced by extracting sodium sulfate from mirabilite and gypsum symbiotic ore, which is different from the gypsum commonly used in the art, and the technical effects that the two can play in the present invention are completely different.
[0011] In the present invention, strongly weathered soft rock is a professional term, which refers to a type of rock with a saturated uniaxial ultimate compressive strength of 5 to 30 MPa and a weathering coefficient of 0.2 to 0.4.
[0012] The lithium slag powder in the present invention is obtained by crushing lithium slag produced as a by-product after lithium is extracted from spodumene ore by sulfuric acid method in the process of lithium refining by sulfuric acid method.
[0013] The granulated blast furnace slag powder in the present invention is obtained by drying and grinding granulated blast furnace slag that meets the GB / T203 standard.
[0014] As a further improvement of the present invention, the strongly weathered soft rock satisfies: particle size ≤ 1.18 mm, water content ≤ 5%.
[0015] As a further improvement of the present invention, the granulated blast furnace slag powder meets the following requirements: mass coefficient ≥ 1.4, specific surface area ≥ 700m 2 / kg, 28d activity index ≥100%.
[0016] As a further improvement of the present invention, the lithium slag powder is obtained by crushing the lithium slag produced as a by-product after lithium extraction from spodumene ore by sulfuric acid method, and meets the following requirements: specific surface area ≥ 700m 2 / kg, 28d activity index ≥100%.
[0017] As a further improvement of the present invention, the silicate cement clinker powder satisfies: tricalcium silicate content ≥ 55% by mass, specific surface area ≥ 350m 2 / kg.
[0018] As a further improvement of the present invention, the mirabilite gypsum satisfies: the total mass percentage content of sodium sulfate and potassium sulfate is ≥ 1%.
[0019] The present invention can be specifically implemented according to the following steps:
[0020] S1, measuring each raw material according to the production raw material formula;
[0021] S2. Take the highly weathered soft rock and determine the total amount of water to be added according to the standard test method; then add water according to 1 / 2 of the total amount of water to the highly weathered soft rock, mix evenly, put it into an airtight container, place it at 20-30° C. and seal it for 18-24 hours to obtain a highly weathered soft rock soil material;
[0022] S3, adding water to the curing agent according to 1 / 2 of the total amount of water added and mixing evenly to obtain a curing agent slurry;
[0023] S4, adding the curing agent slurry to the strongly weathered soft rock and soil material at a uniform speed, controlling the stirring rate to be 200-300 r / min during the adding process, and continuously stirring for 5-20 min to obtain a mixed soil sample;
[0024] S5. The mixed soil sample is statically pressed into shape with a compaction degree of ≥ 98%, thereby obtaining a weathered soft rock road solidification and stabilization material.
[0025] Those skilled in the art will understand that the "determine the total amount of water added according to the standard test method" in the above scheme refers to obtaining the optimal compaction moisture content according to the "Testing Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering" JTG 3441 and JTG E51 standard experimental test methods, and calculating the total amount of water added. The "compaction degree" in step S5 is the ratio of the dry density after compaction to the standard maximum dry density, expressed as a percentage.
[0026] The invention also discloses a weathered soft rock road solidified stabilizing material, which is prepared by the preparation method of the weathered soft rock road solidified stabilizing material of the invention.
[0027] The beneficial effects of the present invention are as follows: the weathered soft rock road solidification stabilization material and the preparation method thereof can significantly improve the water stability and unconfined compressive strength of the weathered soft rock road solidification stabilization material, and reduce carbon emissions during the production process. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the state of the weathered soft rock road solidification stabilization material prepared by the methods of Examples 1 to 4 after being immersed in water for 7 days.
[0029] Figure 2 This is a measured graph of the 7d unlimited compressive strength of the weathered soft rock road solidification and stabilization material prepared by the method of Example 3. DETAILED DESCRIPTION
[0030] The present invention is further described below in conjunction with embodiments.
[0031] Embodiment 1:
[0032] The weathered soft rock road solidification and stabilization material was prepared as follows:
[0033] (1) Measure the raw materials according to the following production raw material formula: 100 parts of strongly weathered soft rock and 8 parts of curing agent;
[0034] The curing agent is composed of the following components in proportion by mass:
[0035] Portland cement clinker powder (tricalcium silicate content of 62% by mass, specific surface area of 353m 2 / kg) 100 parts,
[0036] 114 parts of composite mineral admixture, composed of granulated blast furnace slag powder (mass coefficient is 1.45, specific surface area is 721m 2 / kg, 28d activity index is 112%) and lithium slag powder (the lithium slag produced as a by-product after lithium extraction from spodumene ore by sulfuric acid method is crushed, with a specific surface area of 778m 2 / kg, 28d activity index is 103%) in a mass ratio of 3:1;
[0037] 37 parts of mirabilite gypsum (calcium sulfate dihydrate content is 70.4% by mass, sodium sulfate and potassium sulfate total content is 1.3% by mass).
[0038] 29 parts of quicklime,
[0039] 5.6 parts of sodium dodecylbenzene sulfonate,
[0040] 0.14 parts of monoethanol diisopropanolamine;
[0041] (2) reducing the moisture content of the strongly weathered soft rock to 3.6%, crushing it into particles and passing it through a 1.18 mm square hole sieve, taking the sieve under material for later use; determining the total amount of water to be added according to the standard test method; then adding water according to 1 / 2 of the total amount of water to the sieve under material of the strongly weathered soft rock, mixing it evenly, and then putting it into an airtight container, placing it at 24° C. and sealing it for 20 hours, thereby obtaining a strongly weathered soft rock soil material;
[0042] (3) adding water in an amount of 1 / 2 of the total amount of water to the curing agent and mixing evenly to obtain a curing agent slurry;
[0043] (4) adding the curing agent slurry to the strongly weathered soft rock and soil material at a uniform speed, controlling the stirring rate to 250 r / min during the adding process, and continuously stirring for 6 minutes to obtain a mixed soil sample;
[0044] (5) The mixed soil sample is statically pressed into shape with a compaction degree of 98.3%, thereby obtaining a weathered soft rock road solidified and stabilized material.
[0045] Embodiment 2:
[0046] The weathered soft rock road solidification and stabilization material was prepared as follows:
[0047] (1) Measure the raw materials according to the following production raw material formula: 100 parts of strongly weathered soft rock and 6 parts of curing agent;
[0048] The curing agent is composed of the following components in proportion by mass:
[0049] Portland cement clinker powder (tricalcium silicate content of 62% by mass, specific surface area of 353m 2 / kg) 100 parts,
[0050] 114 parts of composite mineral admixture, composed of granulated blast furnace slag powder (mass coefficient is 1.45, specific surface area is 721m 2 / kg, 28d activity index is 112%) and lithium slag powder (the lithium slag produced as a by-product after lithium extraction from spodumene ore by sulfuric acid method is crushed, with a specific surface area of 778m 2 / kg, 28d activity index is 103%) in a mass ratio of 3:1;
[0051] 37 parts of mirabilite gypsum (calcium sulfate dihydrate content is 70.4% by mass, sodium sulfate and potassium sulfate total content is 1.3% by mass).
[0052] 29 parts of quicklime,
[0053] 5.6 parts of sodium dodecylbenzene sulfonate,
[0054] 0.14 parts of monoethanol diisopropanolamine;
[0055] (2) reducing the moisture content of the strongly weathered soft rock to 3.6%, crushing it into particles and passing it through a 1.18 mm square hole sieve, taking the sieve under material for later use; determining the total amount of water to be added according to the standard test method; then adding water according to 1 / 2 of the total amount of water to the sieve under material of the strongly weathered soft rock, mixing it evenly, and then putting it into an airtight container, placing it at 24° C. and sealing it for 20 hours, thereby obtaining a strongly weathered soft rock soil material;
[0056] (3) adding water in an amount of 1 / 2 of the total amount of water to the curing agent and mixing evenly to obtain a curing agent slurry;
[0057] (4) adding the curing agent slurry to the strongly weathered soft rock and soil material at a uniform speed, controlling the stirring rate to 250 r / min during the adding process, and continuously stirring for 6 minutes to obtain a mixed soil sample;
[0058] (5) The mixed soil sample is statically pressed into shape with a compaction degree of 98.6%, thereby obtaining a weathered soft rock road solidified and stabilized material.
[0059] Embodiment three:
[0060] The weathered soft rock road solidification and stabilization material was prepared as follows:
[0061] (1) Measure the raw materials according to the following production raw material formula: 100 parts of strongly weathered soft rock and 10 parts of curing agent;
[0062] The curing agent is composed of the following components in proportion by mass:
[0063] Portland cement clinker powder (tricalcium silicate content of 58% by mass, specific surface area of 359m 2 / kg) 100 parts,
[0064] 150 parts of composite mineral admixture, made of granulated blast furnace slag powder (mass coefficient 1.45, specific surface area 727m 2 / kg, 28d activity index is 109%) and lithium slag powder (the lithium slag produced as a by-product after lithium extraction from spodumene ore by sulfuric acid method is crushed, with a specific surface area of 742m 2 / kg, 28d activity index is 112%), with a mass ratio of 3.5:1;
[0065] 47 parts of mirabilite gypsum (calcium sulfate dihydrate content is 71.2% by mass, sodium sulfate and potassium sulfate total content is 1.2% by mass).
[0066] 30 parts of quicklime,
[0067] 6.5 parts of sodium dodecylbenzene sulfonate,
[0068] 0.17 parts of monoethanol diisopropanolamine;
[0069] (2) reducing the moisture content of the strongly weathered soft rock to 4.4%, crushing it into particles and passing it through a 1.18 mm square hole sieve, taking the sieve under material for later use; determining the total amount of water added according to the standard test method; then adding water according to 1 / 2 of the total amount of water added to the sieve under material of the strongly weathered soft rock, mixing the mixture evenly, and then placing the mixture in an airtight container, placing the mixture under sealed condition at 24° C. for 22 hours, and obtaining a strongly weathered soft rock soil material;
[0070] (3) adding water in an amount of 1 / 2 of the total amount of water to the curing agent and mixing evenly to obtain a curing agent slurry;
[0071] (4) adding the curing agent slurry to the strongly weathered soft rock and soil material at a uniform speed, controlling the stirring rate to 200 r / min during the adding process, and continuously stirring for 15 min to obtain a mixed soil sample;
[0072] (5) The mixed soil sample is statically pressed into shape with a compaction degree of 98.4%, thereby obtaining a weathered soft rock road solidified and stabilized material.
[0073] Embodiment 4:
[0074] The weathered soft rock road solidification and stabilization material was prepared as follows:
[0075] (1) Measure the raw materials according to the following production raw material formula: 100 parts of strongly weathered soft rock and 5 parts of curing agent;
[0076] The curing agent is composed of the following components in proportion by mass:
[0077] Portland cement clinker powder (tricalcium silicate content of 55% by mass, specific surface area of 350m2 / kg) 100 parts,
[0078] 100 parts of composite mineral admixture, made of granulated blast furnace slag powder (mass coefficient is 1.6, specific surface area is 706m 2 / kg, 28d activity index is 102%) and lithium slag powder (the lithium slag produced as a by-product after lithium extraction from spodumene ore by sulfuric acid method is crushed, with a specific surface area of 702m 2 / kg, 28d activity index is 101%) at a mass ratio of 1.5:1;
[0079] 30 parts of mirabilite gypsum (calcium sulfate dihydrate content is 70.4% by mass, sodium sulfate and potassium sulfate total content is 1.0% by mass).
[0080] 36 parts of quicklime,
[0081] 9 parts of sodium dodecylbenzenesulfonate,
[0082] 0.6 parts of monoethanol diisopropanolamine;
[0083] (2) reducing the moisture content of the strongly weathered soft rock to 4.9%, crushing it into particles and passing it through a 1.18 mm square hole sieve, taking the sieve under material for later use; determining the total amount of water added according to the standard test method; then adding water according to 1 / 2 of the total amount of water added to the sieve under material of the strongly weathered soft rock, mixing the mixture evenly, and then placing the mixture in an airtight container, placing the mixture under sealed condition at 24° C. for 18 hours, and obtaining a strongly weathered soft rock soil material;
[0084] (3) adding water in an amount of 1 / 2 of the total amount of water to the curing agent and mixing evenly to obtain a curing agent slurry;
[0085] (4) adding the curing agent slurry to the strongly weathered soft rock and soil material at a uniform speed, controlling the stirring rate to 200 r / min during the adding process, and continuously stirring for 5 minutes to obtain a mixed soil sample;
[0086] (5) The mixed soil sample is statically pressed into shape with a compaction degree of 98.0%, thereby obtaining a weathered soft rock road solidified and stabilized material.
[0087] Comparative Example 1:
[0088] This comparative example is a control experiment of Example 2, and is implemented under the same conditions and steps as Example 2, with the only difference being that the curing agent is replaced with an equal mass of P·O 42.5 cement. The specific implementation is as follows:
[0089] (1) The raw materials are measured according to the following production raw material formula: 100 parts of strongly weathered soft rock and 6 parts of curing agent; wherein the curing agent is P·O 42.5 cement.
[0090] (2) reducing the moisture content of the strongly weathered soft rock to 3.6%, crushing it into particles and passing it through a 1.18 mm square hole sieve, taking the sieve under material for later use; determining the total amount of water to be added according to the standard test method; then adding water according to 1 / 2 of the total amount of water to the sieve under material of the strongly weathered soft rock, mixing it evenly, and then putting it into an airtight container, placing it at 24° C. and sealing it for 20 hours, thereby obtaining a strongly weathered soft rock soil material;
[0091] (3) adding 1 / 2 of the total amount of water to the P·O 42.5 cement and mixing evenly to obtain a curing agent paste;
[0092] (4) adding the curing agent slurry to the strongly weathered soft rock and soil material at a uniform speed, controlling the stirring rate to 250 r / min during the adding process, and continuously stirring for 6 minutes to obtain a mixed soil sample;
[0093] (5) The mixed soil sample is statically pressed into shape with a compaction degree of 98.6%, thereby obtaining a weathered soft rock road solidified and stabilized material.
[0094] Comparative Example 2:
[0095] This comparative example is a control experiment of Example 2, and is implemented under the same conditions and steps as Example 2, with the only difference being that the mirabilite gypsum is replaced with the composite mineral admixture of the same mass (i.e., the total amount of mirabilite gypsum and the composite mineral admixture is kept unchanged). The specific implementation is as follows:
[0096] (1) Measure the raw materials according to the following production raw material formula: 100 parts of strongly weathered soft rock and 6 parts of curing agent;
[0097] The curing agent is composed of the following components in proportion by mass:
[0098] Portland cement clinker powder (tricalcium silicate content of 62% by mass, specific surface area of 353m 2 / kg) 100 parts,
[0099] 151 parts of composite mineral admixture, made of granulated blast furnace slag powder (mass coefficient is 1.45, specific surface area is 721m 2 / kg, 28d activity index is 112%) and lithium slag powder (the lithium slag produced as a by-product after lithium extraction from spodumene ore by sulfuric acid method is crushed, with a specific surface area of 778m 2 / kg, 28d activity index is 103%) in a mass ratio of 3:1;
[0100] 29 parts of quicklime,
[0101] 5.6 parts of sodium dodecylbenzene sulfonate,
[0102] 0.14 parts of monoethanol diisopropanolamine;
[0103] (2) reducing the moisture content of the strongly weathered soft rock to 3.6%, crushing it into particles and passing it through a 1.18 mm square hole sieve, taking the sieve under material for later use; determining the total amount of water to be added according to the standard test method; then adding water according to 1 / 2 of the total amount of water to the sieve under material of the strongly weathered soft rock, mixing it evenly, and then putting it into an airtight container, placing it at 24° C. and sealing it for 20 hours, thereby obtaining a strongly weathered soft rock soil material;
[0104] (3) adding water in an amount of 1 / 2 of the total amount of water to the curing agent and mixing evenly to obtain a curing agent slurry;
[0105] (4) adding the curing agent slurry to the strongly weathered soft rock and soil material at a uniform speed, controlling the stirring rate to 250 r / min during the adding process, and continuously stirring for 6 minutes to obtain a mixed soil sample;
[0106] (5) The mixed soil sample is statically pressed into shape with a compaction degree of 98.6%, thereby obtaining a weathered soft rock road solidified and stabilized material.
[0107] Comparative Example 3:
[0108] This comparative example is a control experiment of Example 2, and is implemented under the same conditions and steps as Example 2, with the only difference being that the composite mineral admixture is replaced with an equal mass of Glauber's salt gypsum (i.e., the total amount of Glauber's salt gypsum and the composite mineral admixture is kept unchanged). The specific implementation is as follows:
[0109] (1) Measure the raw materials according to the following production raw material formula: 100 parts of strongly weathered soft rock and 6 parts of curing agent;
[0110] The curing agent is composed of the following components in proportion by mass:
[0111] Portland cement clinker powder (tricalcium silicate content of 62% by mass, specific surface area of 353m 2 / kg) 100 parts,
[0112] 151 parts of mirabilite gypsum (calcium sulfate dihydrate content is 70.4% by mass, sodium sulfate and potassium sulfate total content is 1.3% by mass).
[0113] 29 parts of quicklime,
[0114] 5.6 parts of sodium dodecylbenzene sulfonate,
[0115] 0.14 parts of monoethanol diisopropanolamine;
[0116] (2) reducing the moisture content of the strongly weathered soft rock to 3.6%, crushing it into particles and passing it through a 1.18 mm square hole sieve, taking the sieve under material for later use; determining the total amount of water to be added according to the standard test method; then adding water according to 1 / 2 of the total amount of water to the sieve under material of the strongly weathered soft rock, mixing it evenly, and then putting it into an airtight container, placing it at 24° C. and sealing it for 20 hours, thereby obtaining a strongly weathered soft rock soil material;
[0117] (3) adding water in an amount of 1 / 2 of the total amount of water to the curing agent and mixing evenly to obtain a curing agent slurry;
[0118] (4) adding the curing agent slurry to the strongly weathered soft rock and soil material at a uniform speed, controlling the stirring rate to 250 r / min during the adding process, and continuously stirring for 6 minutes to obtain a mixed soil sample;
[0119] (5) The mixed soil sample is statically pressed into shape with a compaction degree of 98.6%, thereby obtaining a weathered soft rock road solidified and stabilized material.
[0120] Comparative Example 4:
[0121] This comparative example is a control experiment of Example 2, and is implemented under the same conditions and steps as Example 2, with the only difference being that the mirabilite gypsum is replaced with gypsum of equal mass.
[0122] (1) Measure the raw materials according to the following production raw material formula: 100 parts of strongly weathered soft rock and 6 parts of curing agent; wherein the curing agent is composed of the following components in the following mass proportions:
[0123] Portland cement clinker powder (tricalcium silicate content of 62% by mass, specific surface area of 353m 2 / kg) 100 parts,
[0124] 114 parts of composite mineral admixture, composed of granulated blast furnace slag powder (mass coefficient is 1.45, specific surface area is 721m 2 / kg, 28d activity index is 112%) and lithium slag powder (the lithium slag produced as a by-product after lithium extraction from spodumene ore by sulfuric acid method is crushed, with a specific surface area of 778m 2 / kg, 28d activity index is 103%) in a mass ratio of 3:1;
[0125] 37 parts of gypsum (calcium sulfate dihydrate content: 72.8% by mass),
[0126] 29 parts of quicklime,
[0127] 5.6 parts of sodium dodecylbenzene sulfonate,
[0128] 0.14 parts of monoethanol diisopropanolamine;
[0129] (2) reducing the moisture content of the strongly weathered soft rock to 3.6%, crushing it into particles and passing it through a 1.18 mm square hole sieve, taking the sieve under material for later use; determining the total amount of water to be added according to the standard test method; then adding water according to 1 / 2 of the total amount of water to the sieve under material of the strongly weathered soft rock, mixing it evenly, and then putting it into an airtight container, placing it at 24° C. and sealing it for 20 hours, thereby obtaining a strongly weathered soft rock soil material;
[0130] (3) adding water in an amount of 1 / 2 of the total amount of water to the curing agent and mixing evenly to obtain a curing agent slurry;
[0131] (4) adding the curing agent slurry to the strongly weathered soft rock and soil material at a uniform speed, controlling the stirring rate to 250 r / min during the adding process, and continuously stirring for 6 minutes to obtain a mixed soil sample;
[0132] (5) The mixed soil sample is statically pressed into shape with a compaction degree of 98.6%, thereby obtaining a weathered soft rock road solidified and stabilized material.
[0133] Comparative experiment on compressive strength and water stability coefficient of weathered soft rock road solidification stabilization materials:
[0134] According to the "Test Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering" JTG 3441-2024 and the "Technical Standard for Application of Soil Stabilizers" CJJ / T 286-2018, the 7d unconfined compressive strength and water stability coefficient of the red layer soft rock roadbed mixture samples in the embodiment and the comparative example were respectively measured. The measurement results are shown in Table 1:
[0135] Table 1 Performance test results of weathered soft rock road solidification stabilization materials
[0136] 7d unconfined compressive strength / MPa Water stability coefficient Embodiment 1 3.56 93 Embodiment 2 4.75 97 Embodiment 3 5.50 94 Embodiment 4 3.43 91 Comparative Example 1 (P·O42.5 cement) 3.15 84 Comparative Example 2 (Single Composite Mineral) 4.76 81 Comparative Example 3 (Single Glauber's Salt Gypsum) 2.26 76 Comparative Example 4 (Gypsum) 4.32 83
[0137] It can be seen from the test results of Examples 1 to 4 in Table 1 that the weathered soft rock road solidification stabilization material prepared by the present invention has excellent compressive strength and water stability coefficient.
[0138] From the comparison between Example 2 and Comparative Example 2 in Table 1, it can be seen that, compared with the solidified and stabilized material produced using strongly weathered soft rock and P·O42.5 cement as raw materials, the curing agent of the present invention can significantly improve the compressive strength and water stability coefficient of the weathered soft rock road solidified and stabilized material.
[0139] From the comparison of Example 2, Comparative Example 2 and Comparative Example 3 in Table 1, it can be seen that when the total amount of composite mineral admixture and Glauber's salt gypsum used is exactly the same, the water stability coefficient of the solidified and stabilized material obtained by Example 2 in which the two are used in combination is significantly higher than that of Comparative Example 2 in which the composite mineral admixture is used alone and Comparative Example 3 in which Glauber's salt gypsum is used alone. It can be seen that the composite mineral admixture and Glauber's salt gypsum in the present invention have a synergistic effect in improving the water stability of the weathered soft rock road solidification and stabilization material.
[0140] From the comparison between Example 2 and Comparative Example 4 in Table 1, it can be seen that after the mirabilite gypsum is replaced by gypsum, the water stability of the solidified stable material is significantly reduced.
Claims
1. A method for preparing weathered soft rock road solidification stabilization material, characterized in that: The production raw material formula includes the following components in proportion by mass: 100 parts of strongly weathered soft rock and 5 to 10 parts of a curing agent; the curing agent is composed of the following components in proportion by mass: 100 parts of Portland cement clinker powder, 100 to 150 parts of a composite mineral admixture, 30 to 45 parts of mirabilite gypsum, 20 to 36 parts of quicklime, 2 to 9 parts of sodium dodecylbenzene sulfonate, and 0.08 to 0.6 parts of monoethanol diisopropanolamine; the composite mineral admixture is composed of granulated blast furnace slag powder and lithium slag powder in a mass ratio of 1.5 to 3.5:
1.
2. The method for preparing the weathered soft rock road solidification stabilization material according to claim 1, characterized in that: The strongly weathered soft rock meets the following requirements: particle size ≤ 1.18 mm, water content ≤ 5%.
3. The method for preparing the weathered soft rock road solidification stabilization material according to claim 1, characterized in that: The granulated blast furnace slag powder meets the following requirements: mass coefficient ≥ 1.4, specific surface area ≥ 700m 2 / kg, 28d activity index ≥100%.
4. The method for preparing weathered soft rock road solidification stabilization material according to claim 1, characterized in that: The lithium slag powder is obtained by crushing the lithium slag produced as a by-product after lithium extraction from spodumene ore by sulfuric acid method, and meets the following requirements: specific surface area ≥ 700m 2 / kg, 28d activity index ≥100%.
5. The method for preparing weathered soft rock road solidification stabilization material according to claim 1, characterized in that: The silicate cement clinker powder meets the following requirements: tricalcium silicate content ≥ 55% by mass, specific surface area ≥ 350m 2 / kg.
6. The method for preparing weathered soft rock road solidification stabilization material according to claim 1, characterized in that: The mirabilite gypsum meets the following requirement: the total mass percentage content of sodium sulfate and potassium sulfate is ≥ 1%.
7. The method for preparing the weathered soft rock road solidification and stabilization material according to any one of claims 1 to 6, characterized in that: The steps include: S1, measuring each raw material according to the production raw material formula; S2, taking the highly weathered soft rock, determining the total amount of water to be added according to the standard test method; then adding water according to 1 / 2 of the total amount of water to the highly weathered soft rock, mixing evenly, and then putting it into an airtight container, placing it at 20-30° C. and sealing it for 18-24 hours to obtain a highly weathered soft rock soil material; S3, adding water to the curing agent according to 1 / 2 of the total amount of water added and mixing evenly to obtain a curing agent slurry; S4, adding the curing agent slurry to the strongly weathered soft rock and soil material at a uniform speed, controlling the stirring rate to be 200-300 r / min during the adding process, and continuously stirring for 5-20 min to obtain a mixed soil sample; S5. The mixed soil sample is statically pressed into shape with a compaction degree of ≥ 98%, thereby obtaining a weathered soft rock road solidification and stabilization material.
8. The weathered soft rock road solidified and stabilized material obtained by the method for preparing the weathered soft rock road solidified and stabilized material according to any one of claims 1 to 7.
